2010
DOI: 10.3322/caac.20074
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Melanoma Diagnosis: 25 Years Beyond the ABCDs

Abstract: Early detection of malignant melanoma remains the key factor in lowering mortality from this cancer. Recognizing the importance of this issue 25 years ago, our group at New York University published in CA: A Cancer Journal for Clinicians the mnemonic "ABCD" to facilitate the early diagnosis of melanoma. Studies have demonstrated the usefulness of this paradigm in enhancing early melanoma diagnosis as a part of clinical examinations, mass screenings, and public education programs. Approaches to melanoma diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
274
0
16

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(301 citation statements)
references
References 111 publications
2
274
0
16
Order By: Relevance
“…Th ere have been no randomized trials performed in patients with IBD assessing this recommendation; however, early detection, including performing regular skin self-examinations and physician skin examinations has been found to result in melanoma diagnoses at earlier stages, when the disease is most treatable ( 120,121 ). Th us, it is suggested that all IBD patients should follow a program of sun protection and dermatological surveillance, which takes into account their other non-IBD-related risk factors for skin cancer development ( 122,123 ). In addition, education on skin cancer risk and rapid referral for skin abnormalities is appropriate in this patient population.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Th ere have been no randomized trials performed in patients with IBD assessing this recommendation; however, early detection, including performing regular skin self-examinations and physician skin examinations has been found to result in melanoma diagnoses at earlier stages, when the disease is most treatable ( 120,121 ). Th us, it is suggested that all IBD patients should follow a program of sun protection and dermatological surveillance, which takes into account their other non-IBD-related risk factors for skin cancer development ( 122,123 ). In addition, education on skin cancer risk and rapid referral for skin abnormalities is appropriate in this patient population.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Melanoma is currently the fifth most frequently diagnosed cancer in the United States and is predicted to account for B65% of all skin cancer deaths in 2010 (Rigel et al, 2010). Melanoma metastases can occur early in the course of disease; therefore, detecting melanoma early is critical for patient survival (Rigel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma metastases can occur early in the course of disease; therefore, detecting melanoma early is critical for patient survival (Rigel et al, 2010). Beyond an early surgical removal of the primary tumor, there is currently no highly effective standard therapy available, especially for more advanced stages (Segura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the only reliable method of distinguishing between dysplastic nevi and melanoma is via stained biopsies, which is invasive and expensive. Clinician specificity for melanoma is approximately 4%, 23,24 which means that roughly 25 more times biopsies are performed than required, translating to an estimated cost of $6 × 10 9 to the US health care system. In 2007, the mean wait time for new patients in urban areas to see a dermatologist was 33 days; in rural areas, the number rises to 46 days.…”
Section: A Skin Cancermentioning
confidence: 99%